Stable isotopes (δ13C, δ15N) seasonal changes in particulate organic matter and in different life stages of anchoveta (Engraulis ringens) in response to local and large scale oceanographic variations in north and central Chile. (July 2020) - Castro, Leonardo R.; González, Valeria; Claramunt, Gabriel; Barrientos, Pamela; Soto, Samuel
Highlights: Coastal upwelling affects similarly the δ 13 C and δ 15 N signatures of POM in different locations along the Humboldt Current. Fresh water intrusions contribute to changes in isotopic signatures at different zones and seasons. More depleted δ 13 C values were observed in winter POM. The trophic positions (TP) of adult anchoveta were higher than those of their larvae and adult TP were unaffected by season. Trophic positions of larval anchoveta were similar between locations. Abstract: We compared the isotopic (δ 13 C, δ 15 N) signals in particulate organic matter (POM), small sized copepods, exogenous feeding larvae, and anchoveta ( Engraulis ringens) eggs and adults, in relation to oceanographic characteristics during this species' reproductive season (late winter – spring, 2016 and 2017) in two spawning zones along the Humboldt Current: northern (Iquique, 20°S) and central Chile (Talcahuano, 36°S). Both zones are subject to wind-driven coastal upwelling (most of the year in Iquique but seasonal in Talcahuano) and differ in freshwater input (higher in winter in Talcahuano and almost null in Iquique). In Talcahuano, lower precipitations and river fluxes occurred in winter 2016 compared with 2017. Our results show that, there are large scale processes that similarly affect the δ 13 C and δ 15 N signatures in different locations along the Humboldt Current (coastal upwelling), but also clear seasonal differences in the sources of δ 13 C and δ 15 N occur locally at the base of the pelagic trophic webs (POM). The seasonal difference in winter δ 13 C is largely due to the influx of terrigenous organic carbon into the Talcahuano coast, product of increased river discharges in normal winter years (2017, δ 13 C POM, winter = −24.78‰ vs spring = −19.16‰). Higher δ 15 N POM values occurred at the start of the upwelling season in spring in both locations during both years (Iquique 2016, δ 15 N: winter = 7.80‰ vs. spring = 10.65‰; Iquique 2017: winter = 10.57‰ vs. spring = 14.95‰) (Talcahuano 2016, δ 15 N: winter = 8.70‰ vs. spring = 9.07‰; Talcahuano 2017: winter = 6.44‰ vs. spring = 9.76‰). In 2017, δ 15 N values of small copepods and exogenous feeding larvae were also higher in spring than winter, but the δ 15 N values in adult anchovetas and their eggs were not, suggesting the seasonal differences in δ 15 N decrease as the trophic position increased. Within seasons, the estimated larval trophic positions were similar across locations (TP = 2.4–2.5) and were lower than those of adults (TP = 3.0–3.4) in Talcahuano in 2017. The overall results suggest that inter-annual and seasonal variations in large scale wind-driven oceanographic processes affect the δ 13 C and δ 15 N signatures at the base of the trophic web with different intensities at different locations and thereby induce variation in the isotopic signatures all along the trophic web but with different magnitude between trophic levels.